Correlation of Thyroid Function Tests and Goitre - Atiq Sadiq , Shahid Mahmood , Eitezaz Ahmed Bashir , Saad Sultan Khan (Journal of Rawalpindi Medical College, 2012)
Background: To correlate the biochemical thyroid profiles with the clinical presentation of patients with enlarged thyroid gland. Methods: In this descriptive study , 100 patients with goiter were selected. Clinical signs of hyper or hypothyroidism were noted. After history and examination, findings were recorded on the proforma and diagnosis was established whether the patient was clinically euthyroid or not. Blood samples were taken for biochemical evaluation to make a comparison of clinical finding with laboratory findings. The spearman correlation coefficient was calculated to determine the correlation between various attributes of the patient with the problem of goiter. A multivariate regression analysis was used to establish the neutrality between the clinical assessment and bio chemical examination (two alternate tests) employed for the evaluation of the status of thyroid in patients with goitre. Results: Sixty eight patients were clinically found to have simple goitre and 62 out of these were confirmed to be so by thyroid function tests. Whereas remaining 6 patients were found toxic biochemically. Clinical diagnosis was accurate in 91.17 % of cases of clinically euthyroid. Thirty two patients were having clinical features of toxicity which was confirmed to be so by biochemical assessment. Accuracy of clinical assessment of toxicity was 100 %. Conclusions: Thyroid status of a patient with goitre can be promptly assessed clinically. Though the importance of thyroid function tests still stand when one or more of clinical features of toxicity make clinical judgment confusing, for medico legal purpose and patients on beta blockers